The Good Enough Teacher - Natalie Davey (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
This paper puts forward a pedagogical model of care for K-12 educators that is specifically focused on alternative classroom educators. In conversation with educational theorists and psychologists, a model of care that is translatable to both teachers and students in non-traditional classrooms is presented. Looking first at Arlie Hochschild’s “emotion work” in the context of alternative classroom teaching, a link is made to Nel Noddings’s “ethics of care” as a pedagogical starting point. The author then riffs on psychoanalyst D.W. Winnicott’s notion of the “good enough mother,” the one who “manages a difficult task: initiating the infant into a world in which he or she will feel both cared for and ready to deal with life’s endless frustrations” (Alpert). Connecting Alpert’s mobilizing of Winnicott to aspects of Noddings’s “caring relation” builds a theoretical bridge that supports and scaffolds the construction of what the author calls the “good enough teacher.” The author also suggests that this pedagogical model of care might also be replicable by students who need to take care of themselves. Throughout the paper examples are drawn from the author’s experiences as a teacher and learner in a variety of alternative education classrooms.
Keywords: Education; Emotional Labor; Pedagogical Model of Care; Alternative Classrooms